Hacking the internship process - Schleien, Zach; Hobbs, Bill ([United States] The La Plata Press, [2016], 2016)
"Hacking the Internship Process is designed to maximize your internship application results. The authors provide a smart, innovative methodology that leads readers through every aspect of winning their dream internship. The book optimizes reader efficiency by combining the most modern technological tools with hacks proven to get results. Follow simple steps in the book to build a powerful referral network, reach out to future bosses, ace interviews, and much more. Hacking the Internship Process is the perfect guide to get you on the path to obtaining the internship you have always wanted and prepare for a successful career in the field of your dreams.-- Back Cover.
Introduction -- Chapter 1: Research job description hack -- Chapter 2: How to craft your elevator pitch -- Chapter 3: Procrastination hack -- Chapter 4: Building a referral strategy -- Chapter 5: Leveraging your university network --Chapter 6: LinkedIn hack -- Chapter 7: Researching companies hack -- Chapter 8: Could I be that person in 5-7 years? -- Chapter 9: Cover letter hack -- Chapter 10: Search companies hack (applying) -- Chapter 11: Meetup hack -- Chapter 12: Albert's list -- Chapter 13: Venture capital hack -- Chapter 14: Hacks, rituals, & routines before an interview -- Chapter 15: Ace the interview -- Chapter 16: The follow-up game -- Chapter 17: Cancellation & how to avoid it -- Chapter 18: You have multiple offers.Now what? -- Chapter 19: Once you finalize your internship -- Conclusion.
Part of the WORK Book Series"
Includes bibliographical references.
Keywords: Practicums; Employees -- -- Training of; Internship programs; School-to-work transition -- United States